Cerebral Blood Flow Autoregulation in Sepsis for the Intensivist: Why Its Monitoring May Be the Future of Individualized Care. (February 2018) - Goodson, Carrie M.; Rosenblatt, Kathryn; Rivera-Lara, Lucia; Nyquist, Paul; Hogue, Charles W.
Cerebral blood flow (CBF) autoregulation maintains consistent blood flow across a range of blood pressures (BPs). Sepsis is a common cause of systemic hypotension and cerebral dysfunction. Guidelines for BP management in sepsis are based on historical concepts of CBF autoregulation that have now evolved with the availability of more precise technology for its measurement. In this article, we provide a narrative review of methods of monitoring CBF autoregulation, the cerebral effects of sepsis, and the current knowledge of CBF autoregulation in sepsis. Current guidelines for BP management in sepsis are based on a goal of maintaining mean arterial pressure (MAP) above the lower limit of CBF autoregulation. Bedside tools are now available to monitor CBF autoregulation continuously. These data reveal that individual BP goals determined from CBF autoregulation monitoring are more variable than previously expected. In patients undergoing cardiac surgery with cardiopulmonary bypass, for example, the lower limit of autoregulation varied between a MAP of 40 to 90 mm Hg. Studies of CBF autoregulation in sepsis suggest patients frequently manifest impaired CBF autoregulation, possibly a result of BP below the lower limit of autoregulation, particularly in early sepsis or with sepsis-associated encephalopathy. This suggests that the present consensus guidelines for BP management in sepsis may expose some patients to both cerebral hypoperfusion and cerebral hyperperfusion, potentially resulting in damage to brain parenchyma. The future use of novel techniques to study and clinically monitor CBF autoregulation could provide insight into the cerebral pathophysiology of sepsis and offer more precise treatments that may improve functional and cognitive outcomes for survivors of sepsis.